Mengukur Tingkat Penerimaan Mahasiswa Pada Inovasi Digital: Studi Kasus Aplikasi iMagelang - Fadhillah, Annisa; Nabilla, Rhainaya; Nugraha, Joko Tri (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2025)
This study aims to explore students' acceptance of the iMagelang application as an information technology medium in the context of higher education. A quantitative approach was employed, referring to the Technology Acceptance Model (TAM) to analyze the influence of perceived usefulness and perceived ease of use on behavioral intention. Data were collected through questionnaires completed by 98 students from Universitas Tidar. The results show that perceived usefulness has a more significant influence on behavioral intention compared to perceived ease of use. Despite efforts made by the developers to promote the application, challenges remain in enhancing user satisfaction and increasing the number of active users. These findings indicate that digital applications such as iMagelang hold great potential in supporting information access and improving students' digital literacy. However, further development is needed, particularly in enhancing relevant features and implementing effective promotional strategies. Additionally, this study provides valuable insights for the development of public service applications in the digital era, especially in the higher education sector. The practical implications of this study highlight the importance of understanding user needs to create applications that are not only functional but also offer an optimal user experience. This research is expected to serve as a reference for other public service application developers to improve the effectiveness of digital technology in supporting information services